Clinical Usefulness of Novel Serum and Imaging Biomarkers in Risk Stratification of Patients with Stable Angina. (18th June 2014) - Tsaknis, George; Tsangaris, Iraklis; Ikonomidis, Ignatios; Tsantes, Argirios
Abstract : Inflammatory mediators appear to be the most intriguing yet confusing subject, regarding the management of patients with acute coronary syndromes (ACS). The current inflammatory concept of atherosclerotic coronary artery disease (CAD) led many investigators to concentrate on systemic markers of inflammation, as well as imaging techniques, which may be helpful in risk stratification and prognosis assessment for cardiovascular events. In this review, we try to depict many of the recently studied markers regarding stable angina (SA), their clinical usefulness, and possible future applications in the field.